Memanfaatkan Limbah Sedotan Plastik Menjadi Vas Bunga Hias - Halimatusa’diyah, Enni; Fadhila, Puan; Amirah, Nurul (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This journal is being kept to learn more about the process of making flower pots out of plastic straws. A qualitative descriptive research method is employed with this kind of literature review investigation. The findings demonstrated that recycling plastic garbage into flower pots is a step toward reducing plastic waste, as it is well known that plastic waste cannot degrade naturally. Making flower pots out of plastic garbage has a variety of purposes, including: By employing plastic trash as a primary component of flower pots, which can be reused and does not end up as waste in the environment, it is possible to reduce the amount of plastic waste in the environment. Keywords: Waste Plastic Straws, Flower Pots